Pelatihan Peningkatan Keterampilan Guru SMA dalam Mengembangkan Powerpoint Interaktif dengan Kecerdasan Buatan (Artificial Intelligence) - Nurmida Catherine Sitompul; Achmad Noor Fatirul; Andri Kurniawan; Siti Mutmainah (Universitas Negeri Malang, 2024)
Abstract: Instructional media is the core of the Instructional delivery strategy so that learning content can be delivered and received well by students. The PowerPoint program or more often abbreviated as PPT, is the most widely used instructional media both basic and extended. The presence of Artificial intelligence makes the Powerpoint Program can be developed very extended so that it can be used for various characteristics of the field of study that need to be conveyed with various forms of media or multimedia platforms so that it can increase the interaction between students and learning materials. Pengabdian kepada Masyarakat (Community Service), with Subtheme: Training on the Development of Interactive Power Points and Intuitive Displays to Improve Interaction in Learning at SMA Negeri 1 Driyorejo, Gresik. smoothly and in accordance with the even semester period of the 2023-2024 academic year